Preoperative Chronic Opioid Use and Its Effects on Total Knee Arthroplasty Outcomes - Kim, Kelvin; Chen, Kevin; Anoushiravani, Afshin A.; Roof, Mackenzie; Long, William J.; Schwarzkopf, Ran (The Journal of Knee Surgery, 2020)
Unsafe opioid distribution remains a major concern among the total knee arthroplasty (TKA) population. Perioperative opioid use has been shown to be associated with poorer outcomes in patients undergoing TKA including longer length of stay (LOS) and discharges to extended care facilities. The current study aims to detail perioperative opioid use patterns and investigate the effects of preoperative chronic opioid use on perioperative quality outcomes in TKA patients. A retrospective analysis was performed on 338 consecutive TKAs conducted at our institution. Two cohorts were compared in this study—preoperative chronic opioid users and nonchronic opioid users. Opioid usage patterns and quality metrics were collected and analyzed over a 3-month preoperative and a 6-month postoperative period. Fifty-four (16.0%) preoperative chronic opioid users were identified out of the total 338 patients included in the study. Preoperative chronic opioid users experienced significantly longer LOS (2.9 vs 2.6 days; p = 0.026). Patients who remained persistent chronic users throughout the preoperative and postoperative stages demonstrated a significantly longer LOS (3.4 days vs 2.5 days; p = 0.017) compared with those who were no longer chronically using opioids by the 6 months postoperative period. By the 6 months postoperative time point, preoperative chronic users were consuming eight times the morphine-equivalents (mg/day) compared with nonchronic users (p < 0.001). Preoperative chronic opioid use was associated with substantially higher usage patterns throughout the postoperative stages. Such opioid use patterns were associated with longer LOS. Given that perioperative chronic opioid use has shown to negatively impact TKA outcomes, future studies refining current perioperative management strategies are warranted. This is a Level II, prognostic study.
Keywords: total knee arthroplasty; chronic opioid; value-based care; quality outcomes